Efficiency of using alternative sources of heat in electric melting of metal - S. V. Korneev; I. A. Trusova (Литьë и металлургия)
The paper considers ways to assess the efficiency of using alternative sources of heat when melting alloys in electric arc furnaces. The focus is on increasing furnace productivity and reducing production costs. The analysis of the use of various systems for intensifying melting in arc furnaces and their main indicators is carried out. An assessment of the efficiency of fuel use in electric arc furnaces has been carried out. The expected economic effect from the introduction of alternative energy sources in electric furnaces has been calculated. It is shown that the economic effect from the introduction of alternative energy sources on electric arc furnaces depends significantly on the increase in furnace productivity.